A Tool of Conversation: Chatbot - Dahiya, M (International Journal of Computer Sciences and Engineering, 2025)
Chatbot is widely popular now-a-days and catching speed as an application of computer communication. Some programs respond intelligently like human. This type of program is called a Chatbot. This paper addresses the design and implementation of a Chatbot system. We will also study another application where Chatbots could be useful and techniques used while designing a Chatbot.